Comparison of antifungal activity against plant pathogens using essential oils of Cinnamomum spp gender - Rojas-Amado, Angie Geraldine (2023)
The spread of pests affects different plant species generating a challenge for maintaining food safety control, different investigations agree that the permanent use of chemical pesticides generates long-term health conditions in the different biotic and abiotic communities, as well as causing resistance in the different phytopathogens to the chemical components that pesticides contain, which promotes the proliferation of these microorganisms. In the search for solutions to this problem, several investigations have been developed, of which a wide and promising field is the use of essential oils (EA) from different plants, these investigations have shown positive results in the inhibition of antifungal activity. This review article is carried out in order to compare the inhibitory effect of three oils of the genus Cinnamomum spp., Cinnamomum zeylanicum, Cinnamomum cassia and Cinnamomum camphora against three phytopathogenic fungi, Alternaria solani, Fusarium oxysporum and Rhizoctonia solani distributed in the soil worldwide, analyzing which is the extraction method and the most frequently used chemical characterization method, additionally the results obtained by different authors are compared regarding the inhibitory activity that these EA have in the mentioned phytopathogens at different MICs obtaining variable conclusions . Cinnamomum zeylanicum, seems to be the most studied essential oil against three species of fungi mentioned so far and presents a promising antifungal for new pest control technologies, it is proposed to continue investigating the inhibitory behavior of cinnamon oil.